(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Kolesina K.Y. Keywords: metaproject education, metaproject, semantic framework, semantic activity. The article focuses on the stages of metaproject education in terms of semantic framework flow in the process of project activity of students. Five stages in succession are highlighted: 1. Introduction of metasubject project activity. Actualisation of personal intention. 2. Stating the problem of metaproject. Framing of semantic mindsets. 3. “Plunging” into the project. Originating basic system of intentions. 4. Metaproject development in terms of information support. Actualisation of semantic scope of students. 5. The results of project activity. Semantic reflection. Conclusion: semantic actualization of metaproject education highly motivates the efficiency of the whole process of projecting.